2019
DOI: 10.1055/s-0039-1697978
|View full text |Cite
|
Sign up to set email alerts
|

A 13-Year-Old Boy Who Has Kawasaki Disease Shock Syndrome Presents with Parotitis

Abstract: We report a 13-year-old boy who (initially) had symptoms of toxic shock-like syndrome and mumps. Then, the patient was hospitalized in the pediatric intensive care unit (PICU) because of his ongoing hemodynamic instability (low blood pressure of 70/30 mm Hg and capillary refill time of > 4 seconds). During his stay in the PICU, the patient was treated with fluid resuscitation and vasoactive infusion and at the same time was diagnosed with Kawasaki disease shock syndrome (KDSS), when giant right coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In 1975, Kato et al [6] reported a case of severe complications such as shock and heart failure in a 6-monthold child with KD. Since then, this critically ill KD with hemodynamic changes has been reported by successive investigators [7][8][9][10][11]. In 2009, Kanegaye et al [12] first formally defined hemodynamically unstable Kawasaki disease as Kawasaki disease shock syndrome (KDSS), which accounts for approximately (1.9∼7.0)% of all KD.…”
Section: Introductionmentioning
confidence: 99%
“…In 1975, Kato et al [6] reported a case of severe complications such as shock and heart failure in a 6-monthold child with KD. Since then, this critically ill KD with hemodynamic changes has been reported by successive investigators [7][8][9][10][11]. In 2009, Kanegaye et al [12] first formally defined hemodynamically unstable Kawasaki disease as Kawasaki disease shock syndrome (KDSS), which accounts for approximately (1.9∼7.0)% of all KD.…”
Section: Introductionmentioning
confidence: 99%